Diaphragm coating slurry, preparation method thereof and battery diaphragm
By using polyvinylidene fluoride porous microspheres to coat the slurry, the problem of insufficient adhesion of the electrode sheet of the lithium-ion battery separator is solved, and stronger adhesiveness to the electrode sheet and diaphragm and better battery cycle life are achieved.
Patent Information
- Application Number
- CN202411629606.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-03-07
AI Technical Summary
The pole adhesive strength of the existing lithium-ion battery separator is insufficient, resulting in poor battery cell performance and affecting the cycle life of the battery.
Polyvinylidene fluoride porous microspheres are used as the main component of the slurry for coating the slurry. The amphiphilicity and adhesion of the coating are improved through the elongated pore structure and porous nanostructure, and the adhesion strength of the electrode sheet and the diaphragm are enhanced.
It significantly improves the bonding strength and interface compatibility between the electrode sheet and the separator, improves the shaping and transportation performance of the battery cell, and extends the cycle life of the battery.
Smart Images

Figure CN119581792A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of battery separators, and more specifically to a separator coating slurry, a preparation method thereof, and a battery separator. Background Art
[0002] Lithium-ion batteries (LIBs) are widely used in consumer electronics, electric vehicles, and power storage. They are mainly composed of positive electrodes, negative electrodes, separators, and electrolytes. Among them, the separator is one of the key internal components. The performance of the separator determines the interface structure and internal resistance of the battery, and directly affects the battery's capacity, cycle, and safety performance. Excellent separators play an important role in improving the overall performance of the battery. The function of the separator is to separate the positive and negative electrodes of the battery, prevent the battery from short-circuiting, and provide an ion transmission channel. Usually, lithium-ion battery separators are polyolefin porous membranes made of polymer materials such as polypropylene and polyethylene. Since this material has the characteristics of liquid-repellent surface and low surface energy, it has poor wettability to electrolytes. In addition, the surface of the polyolefin separator lacks groups that interact with battery electrodes and electrolytes, and there is almost no adhesion between the battery electrodes. Therefore, air is easily introduced during the battery cell stacking or winding process, the base film and the electrode are not closely attached, and wrinkles are easily generated on the surface, which leads to poor battery cell performance and affects the battery cycle life.
[0003] At present, the method of coating the surface of the diaphragm with polyvinylidene fluoride (PVDF) is usually adopted to solve this interface problem. During the cell winding process, the PVDF-coated diaphragm effectively bonds the pole piece and the diaphragm, can remove the air in the gap inside the cell, reduce the diaphragm wrinkles, increase the hardness of the cell, maintain the consistency of the cell thickness, and facilitate the shaping and transportation of the cell.
[0004] However, the current PVDF coating film has the problem of weak adhesion with the positive electrode sheet (80°C, 2MPa is about 1N / m), which makes it difficult to meet the needs of battery cells. Summary of the invention
[0005] The present application provides a diaphragm coating slurry and a preparation method thereof, and a battery diaphragm, which can improve the adhesion between the diaphragm and the electrode.
[0006] The present application provides a membrane coating slurry, comprising polyvinylidene fluoride porous microspheres; the polyvinylidene fluoride porous microspheres have a narrow and long pore structure, and the average pore size of the polyvinylidene fluoride porous microspheres is less than 50 nm.
[0007] In an optional embodiment, the D50 particle size of the polyvinylidene fluoride porous microspheres is 1 μm-10 μm.
[0008] In an optional embodiment, the melting point of the polyvinylidene fluoride porous microspheres is 80°C-130°C.
[0009] In an optional embodiment, the method for preparing the polyvinylidene fluoride porous microspheres comprises:
[0010] Drying the polyvinylidene fluoride, the acrylic polymer and the lactic acid polymer;
[0011] The dried polyvinylidene fluoride, acrylic polymer and lactic acid polymer are melt-blended according to a ratio, and then the mixture is cooled to room temperature;
[0012] The mixture cooled to room temperature is subjected to melting and cooling crystallization treatments in sequence to obtain a crystalline nanostructure;
[0013] An extracting solution is added into the nanostructure to extract the acrylic polymer and the lactic acid polymer, so as to obtain porous polyvinylidene fluoride porous microspheres with a porous nanostructure.
[0014] In an optional embodiment, the preparation of the polyvinylidene fluoride porous microspheres further includes adding a compatibilizer to the polyvinylidene fluoride, the acrylic polymer and the lactic acid polymer according to a proportion, and then melt blending them.
[0015] In an optional embodiment, when preparing the polyvinylidene fluoride porous microspheres, at least one of the conditions (1) to (5) is satisfied:
[0016] (1) The mass ratio of the polyvinylidene fluoride to the acrylic ester polymer is 1:0.3-1:3;
[0017] (2) The mass ratio of the total mass of the polyvinylidene fluoride and the acrylic ester polymer to the mass ratio of the lactic acid polymer is 1:1-1:11;
[0018] (3) the mass percentage of the compatibilizer in the mixture of the polyvinylidene fluoride, the acrylic polymer and the lactic acid polymer is 0.01%-0.1%;
[0019] (4) the acrylic ester polymer includes an acrylic ester copolymer including at least one of polymethyl methacrylate, polymethacrylate, polyethyl acrylate and polymethyl acrylate;
[0020] (5) The lactic acid polymer includes at least one of dextrorotatory polylactic acid, levorotatory polylactic acid, racemic polylactic acid and optically inactive polylactic acid.
[0021] The present application provides a method for preparing a diaphragm coating slurry, comprising the following steps:
[0022] The porous polyvinylidene fluoride microspheres, a surfactant and an adhesive are mixed and dispersed in a solvent to prepare the membrane coating slurry.
[0023] In an optional embodiment, the step of preparing the diaphragm coating slurry comprises:
[0024] The polyvinylidene fluoride porous microspheres, the surfactant and part of the solvent are mixed and stirred in a spiral rotating manner to prepare a mixed liquid system;
[0025] The mixed liquid system is diluted with the remaining amount of the solvent and ground, and then the adhesive is added and stirred to form the membrane coating slurry.
[0026] In an optional embodiment, the method for preparing the diaphragm coating slurry satisfies at least one of the conditions (1) to (4):
[0027] (1) The solid content of the mixed liquid system is ≥56%;
[0028] (2) In the mixed liquid system, the mass percentage of the surfactant is 1%-20%;
[0029] (3) In the mixed liquid system, the mass percentage of the polyvinylidene fluoride porous microspheres is 55%-95%;
[0030] (4) In the membrane coating slurry, the mass ratio of the polyvinylidene fluoride porous microspheres to the adhesive is 100:(5-15).
[0031] The present application provides a battery separator, comprising a porous substrate and a coating disposed on at least one surface of the porous substrate; the coating is prepared using the separator coating slurry as described above or the separator coating slurry prepared by the preparation method as described above.
[0032] According to the membrane coating slurry in the above embodiment, it includes polyvinylidene fluoride porous microspheres, which have a narrow and long pore structure and an average pore size of less than 50nm. Since the polyvinylidene fluoride porous microspheres have multiple narrow and long pore structures, they have a good specific surface area, and also have the advantages of low density and good stability, which can improve the amphiphilicity of the coating. On the one hand, it can improve the bonding strength between the pole piece and the diaphragm while also improving the interface compatibility between the pole piece and the diaphragm. On the other hand, it can also give the coating and the substrate layer better adhesion, avoid the coating from falling off, and improve the stability of the diaphragm. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 A schematic diagram of a process for preparing porous polyvinylidene fluoride microspheres in an embodiment;
[0034] Figure 2 It is a schematic diagram of the process of preparing a diaphragm coating slurry in an embodiment. DETAILED DESCRIPTION
[0035] The present application is further described in detail below by specific embodiments in conjunction with the accompanying drawings. Wherein similar elements in different embodiments adopt associated similar element numbers. In the following embodiments, many detailed descriptions are intended to enable the present application to be better understood. However, those skilled in the art can easily recognize that some of the features can be omitted in different situations, or can be replaced by other elements, materials, and methods. In some cases, some operations related to the present application are not shown or described in the specification, in order to avoid the core part of the present application being overwhelmed by too much description, and for those skilled in the art, it is not necessary to describe these related operations in detail, and they can fully understand the related operations based on the description in the specification and the general technical knowledge in the art.
[0036] In addition, the features, operations or characteristics described in the specification can be combined in any appropriate manner to form various implementations, and the operation steps involved in each embodiment can also be replaced or adjusted in a sequence in a manner that is obvious to those skilled in the art. Therefore, the specification and drawings are only for the purpose of clearly describing a certain embodiment and do not mean that the composition and / or sequence are necessary.
[0037] The serial numbers of the components in this document, such as "first", "second", etc., are only used to distinguish the objects described and do not have any order or technical meaning. The "connection" and "coupling" mentioned in this application, unless otherwise specified, include direct and indirect connections (couplings).
[0038] The "diaphragm" referred to in this application is an important component of the secondary battery cell. The diaphragm is a thin film used to separate the positive and negative electrodes during the electrolysis reaction to prevent the loss of energy in the direct reaction. The performance of the diaphragm determines the interface structure and internal resistance of the battery, and directly affects the battery's capacity, cycle and safety performance. A diaphragm with excellent performance plays an important role in improving the overall performance of the battery.
[0039] Secondary batteries refer to batteries that can be used again by recharging the active materials after the battery is discharged. This type of battery usually uses the reversibility of chemical reactions, that is, after a chemical reaction is converted into electrical energy, the chemical system can be repaired with electrical energy, and then converted into electrical energy by chemical reaction again. Among them, the more common secondary batteries include but are not limited to nickel-metal hydride batteries, nickel-cadmium batteries, lead-acid (or lead storage) batteries, lithium-ion batteries, polymer lithium-ion batteries, sodium-ion batteries, etc.
[0040] The present application discloses a diaphragm which can be used in a secondary battery. The diaphragm includes a substrate layer and a coating formed by a diaphragm coating slurry disposed on at least one surface of the substrate layer. The diaphragm coating slurry includes polyvinylidene fluoride porous microspheres. The polyvinylidene fluoride porous microspheres have a narrow and long pore structure and an average pore size of less than 50nm. For example, the average pore size of the polyvinylidene fluoride porous microspheres is 20nm, 30nm, 40nm or 45nm. Since the porous polyvinylidene fluoride microspheres have multiple narrow and long pore structures, they have the advantages of large specific surface area, low density and good stability. Different from the existing solid polyvinylidene fluoride microspheres or porous microspheres with a core-shell structure prepared from polyvinylidene fluoride secondary particles, the porous polyvinylidene fluoride microspheres in the present application have better capillary action. In the process of preparing the coating slurry, other coating components can be effectively adsorbed to improve the dispersibility of the slurry, thereby improving the amphiphilicity of the coating, improving the bonding strength between the electrode and the diaphragm, and also improving the interface compatibility between the electrode and the diaphragm. It can also give the coating and the substrate layer better adhesion, avoid coating shedding, and improve the stability of the diaphragm.
[0041] In some embodiments, the D50 particle size of the porous polyvinylidene fluoride microspheres is 1 μm-10 μm. For example, the particle size of the porous microspheres is 2 μm, 5 μm or 10 μm. Controlling the size of the porous polyvinylidene fluoride microspheres facilitates uniform coating of the slurry, which is beneficial to improving the uniformity and consistency of the performance of the diaphragm.
[0042] In some embodiments, the melting point of the porous polyvinylidene fluoride microspheres is 80° C.-130° C. For example, the melting point of the porous polyvinylidene fluoride microspheres is 80° C., 90° C., 100° C., 110° C., 120° C., or 130° C. Controlling the melting point of the porous polyvinylidene fluoride microspheres helps improve the bonding performance of the separator at room temperature, thereby helping to reduce the production cost.
[0043] See also Figure 1 The method for preparing the above-mentioned porous polyvinylidene fluoride microspheres comprises:
[0044] S101: drying the polyvinylidene fluoride, the acrylic acid polymer and the lactic acid polymer.
[0045] Specifically, polyvinylidene fluoride, acrylic polymer and lactic acid polymer are placed in an oven and dried at a preset temperature so that the polyvinylidene fluoride, acrylic polymer and lactic acid polymer are dried for subsequent melting treatment. The preset temperature is preferably 80° C. and the drying time is 12 hours.
[0046] In some embodiments, the acrylic polymer includes an acrylic copolymer including at least one of polymethyl methacrylate (PMMA), polymethacrylate, polyethyl acrylate and polymethyl acrylate; the lactic acid polymer includes at least one of left-handed polylactic acid (PLLA), right-handed polylactic acid, racemic polylactic acid and optically inactive polylactic acid. Further, the acrylic polymer includes polymethyl methacrylate (PMMA), and the lactic acid polymer includes left-handed polylactic acid (PLLA).
[0047] S102: melt-blending the dried polyvinylidene fluoride, acrylic polymer and lactic acid polymer according to a ratio, and then cooling the mixture to room temperature.
[0048] Specifically, the dried polyvinylidene fluoride, acrylic acid polymer and lactic acid polymer are added into an internal mixer according to a proportion, and are roughly mixed and finely mixed to achieve melt blending.
[0049] In some embodiments, the temperature during melt blending is 150°C-250°C, the rotor speed of the internal mixer during rough mixing is 10rpm / min-50rpm / min, and the rough mixing time is 1min-10min. The rotor speed of the internal mixer during fine mixing is 50rpm / min-100rpm / min, and the fine mixing time is 5min-30min.
[0050] In some embodiments, the mass ratio of polyvinylidene fluoride to acrylic polymer is 1:0.3-1:3. For example, the mass ratio of polyvinylidene fluoride to acrylic polymer is 3:1, 2:1, 1:1, 1:2 or 1:3. By adjusting the mass ratio of polyvinylidene fluoride to acrylic polymer, the pore size of polyvinylidene fluoride porous microspheres can be adjusted, which helps to improve the performance of the diaphragm.
[0051] In some embodiments, the mass ratio of the total mass of polyvinylidene fluoride and acrylic polymer to the mass ratio of lactic acid polymer is 1:1-1:11. For example, the mass ratio of the total mass of polyvinylidene fluoride and acrylic polymer to the mass ratio of lactic acid polymer is 1:1, 1:2, 1:3, 1:4, 1:6, 1:7, 1:9 or 1:10. By controlling the mass ratio of the total mass of polyvinylidene fluoride and acrylic polymer to the mass ratio of lactic acid polymer, the size of the porous microspheres of polyvinylidene fluoride and the size of the pore structure can be regulated to improve the lyophilicity of the coating, thereby improving the bonding performance of the diaphragm.
[0052] In some embodiments, the preparation of polyvinylidene fluoride porous microspheres also includes adding a compatibilizer. The role of the compatibilizer is to improve the poor compatibility of most polymers when blended, and its specific role is to increase interfacial tension. In some embodiments, the compatibilizer uses an acrylic copolymer, for example, in the embodiment of the present application, the compatibilizer uses a copolymer of methacrylate glycidyl methacrylate (P(MMA-co-GMA)).
[0053] In some embodiments, the mass percentage of the compatibilizer in the mixture of polyvinylidene fluoride, acrylic polymer and lactic acid polymer is 0.01%-0.1%. For example, the compatibilizer accounts for 0.01%, 0.05% or 0.1% of the total amount of the mixture of polyvinylidene fluoride, acrylic polymer and lactic acid polymer. When preparing polyvinylidene fluoride porous microspheres, it is possible to choose whether to add a compatibilizer or adjust the added content of the compatibilizer. Preferably, the mass percentage of the compatibilizer in the mixture of polyvinylidene fluoride, acrylic polymer and lactic acid polymer is 0.05%-0.1%. The addition of the compatibilizer can further reduce the size of the porous microspheres, thereby contributing to the improvement of the uniformity and bonding effect of the diaphragm coating. The increase in the content of the compatibilizer increases the number of pores in the finally prepared polyvinylidene fluoride (PVDF) porous microspheres, increases their specific surface area, and can enhance the adsorption of surfactants, thereby reducing their own bonding effect. Therefore, the content of the compatibilizer should be reasonably controlled to enhance the bonding force of the polyvinylidene fluoride (PVDF) porous microspheres and ultimately improve the bonding performance of the diaphragm.
[0054] When adding the compatibilizer, the above step S102 specifically includes: melt-blending the polyvinylidene fluoride, the acrylic polymer, the lactic acid polymer and the compatibilizer according to a proportion, and then cooling the mixture to room temperature.
[0055] S103: The mixture cooled to room temperature is subjected to melting and cooling crystallization treatments in sequence to obtain a crystalline nanostructure.
[0056] Specifically, the mixture is subjected to melting and cooling crystallization treatment in sequence to obtain a crystalline nanostructure, specifically comprising: placing the mixture in an oven to melt and then cooling, the melting temperature is 200°C-250°C, the melting time is 5min-20min, the cooling temperature is 100°C-150°C, and the cooling time is not less than 24h.
[0057] S104: adding an extracting solution into the nanostructure to extract the acrylic polymer and the lactic acid polymer to obtain porous polyvinylidene fluoride porous microspheres with a porous nanostructure.
[0058] Specifically, an extracting solution is added to the crystallized mixture to remove the acrylic acid polymer and the lactic acid polymer to obtain polyvinylidene fluoride porous microspheres, which specifically includes: extracting by Soxhlet extraction, the extracting solution is a good solvent for the acrylic acid polymer and the lactic acid polymer, the heating temperature is controlled so that the extracting solution refluxes once every 6 minutes to 8 minutes, and the extraction time is 6 hours to 12 hours. After the extraction is completed, the microspheres are taken out and placed in ethanol for a first preset time, and then transferred to deionized water for a second preset time to obtain wet polyvinylidene fluoride porous microspheres, and the wet polyvinylidene fluoride (PVDF) porous microspheres are freeze-dried to obtain dry polyvinylidene fluoride (PVDF) porous microspheres.
[0059] The first preset time and the second preset time are both 1h-3h. Preferably, the first preset time and the second preset time are both 2h. Sufficient time in ethanol and deionized water can further remove the residues of acrylic acid polymer and lactic acid polymer to obtain wet and higher purity polyvinylidene fluoride (PVDF) porous microspheres.
[0060] During the preparation of porous microspheres, since polyvinylidene fluoride (PVDF) and acrylic polymers have good compatibility, polyvinylidene fluoride (PVDF) and acrylic polymers are mixed into one phase, and the lactic acid polymer forms an independent phase. Subsequently, during the cooling and crystallization process, polyvinylidene fluoride (PVDF) crystallizes in the polyvinylidene fluoride (PVDF) and acrylic polymer phases, inducing phase enrichment to form a nanostructure. Then, a selective solvent (such as chloroform) that can fully dissolve acrylic polymers and lactic acid polymers is selected to remove acrylic polymers and lactic acid polymers, leaving only polyvinylidene fluoride. The removal of acrylic polymers and lactic acid polymers forms multiple pore structures in the above nanostructure, ultimately forming polyvinylidene fluoride (PVDF) porous microspheres with a nanoscale porous structure.
[0061] The present application also provides a method for preparing a coating slurry, wherein the coating slurry includes the above-mentioned polyvinylidene fluoride porous microspheres, and the steps include mixing and dispersing the polyvinylidene fluoride porous microspheres, a surfactant and an adhesive in a solvent to prepare the diaphragm coating slurry.
[0062] See also Figure 2 In some embodiments, the method for preparing the membrane coating slurry comprises:
[0063] S201: mixing polyvinylidene fluoride porous microspheres, a surfactant and a portion of a solvent (e.g., deionized water), and stirring by high-speed spiral rotation to prepare a mixed liquid system;
[0064] S202: Use the remaining solvent (such as deionized water) to dilute the mixed liquid system and grind it, then add the adhesive and stir to form a diaphragm coating slurry.
[0065] In the process of preparing the coating slurry containing polyvinylidene fluoride porous microspheres, dry powdered polyvinylidene fluoride porous microspheres are selected, and then a surfactant is added to the mixing chamber of the mixer for high-speed rotation. With the help of the friction between the surface of the stirring blade with a certain inclination angle and the polyvinylidene fluoride porous microspheres, the polyvinylidene fluoride porous microspheres can move tangentially along the blades. At the same time, due to the action of centrifugal force, the polyvinylidene fluoride porous microspheres are thrown to the inner wall of the mixing chamber and rise along the wall. When they rise to a certain height, they fall back to the center of the stirring blade due to gravity, and then the polyvinylidene fluoride porous microspheres are thrown up again, and the stirring is completed in this cycle. Due to the combination of rising motion and tangential motion, the polyvinylidene fluoride porous microspheres are in a continuous spiral motion state. Since the impeller rotates at a high speed, the material moves at a very fast speed, and the fast-moving particles collide and rub against each other, causing the particles or clumps that are gathered together to be broken up. At the same time, the temperature of the material also rises accordingly, which is beneficial to increase the surface area of the polyvinylidene fluoride (PVDF) powder and increase the adsorption of surfactants, thereby improving the amphiphilicity of the coating.
[0066] It should be noted that tangential motion refers to the movement of an object in a direction tangent to the curve when it moves along the curve.
[0067] In some embodiments, in the mixed liquid system, the solid content of the mixed liquid system is ≥56%. By mixing polyvinylidene fluoride (PVDF) porous microspheres and surfactants at a higher solid content to prepare a mixed liquid system with the above solid content, the dispersion of polyvinylidene fluoride (PVDF) porous microspheres in the aqueous slurry can be greatly improved, while effectively ensuring the realization of the basic functions of the subsequent prepared diaphragm, the mechanical strength of the diaphragm surface can also be improved, and the bonding performance of the diaphragm surface can be effectively guaranteed. For example, the solid content of the mixed liquid system is 56%, 60%, 70%, 80%, 90% or 96%. Preferably, the solid content of the mixed liquid system is 56%-96%. Further, the solid content of the mixed liquid system is 60%-80%.
[0068] In some embodiments, in the mixed liquid system, the mass percentage of the polyvinylidene fluoride (PVDF) porous microspheres includes 55%-95%. For example, the mass percentage of the polyvinylidene fluoride (PVDF) porous microspheres is 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90% or 95%. The mass percentage of the polyvinylidene fluoride (PVDF) porous microspheres within the above range can make the surfactant more evenly distributed between the polyvinylidene fluoride (PVDF) porous microspheres, thereby improving the dispersibility and uniformity of the polyvinylidene fluoride (PVDF) porous microspheres in the slurry.
[0069] In some embodiments, in the mixed liquid system, the mass percentage of the surfactant is 1%-20%. For example, the mass percentage of the surfactant is 1%, 5%, 10%, 15% or 20%. When the content of the surfactant increases, it is beneficial to improve the adhesion between the coating and the substrate layer, but too much surfactant will also reduce the adhesion of the coating to the electrode. Therefore, controlling the mass percentage of the surfactant in the mixed liquid system within the above range can effectively ensure that the porous microspheres can fully adsorb the surfactant to enhance the lyophilicity of the coating, thereby improving the diaphragm and bonding performance.
[0070] In some embodiments, the stirring speed during high-speed spiral rotation stirring is 400rpm-1000rpm, for example, the stirring speed during high-speed spiral rotation stirring is 400rpm, 500rpm, 600rpm, 700rpm, 800rpm, 900rpm or 1000rpm, and the stirring time is 1h-6h, for example, the stirring time is 1h, 2h, 3h, 4h, 5h or 6h. By controlling the stirring speed and stirring time of high-speed spiral rotation within the above range, the porous microspheres can be fully crushed, so that the porous microspheres can be formed into a powder that is more convenient for adsorption with surfactants.
[0071] In some embodiments, after the high-speed spirally rotating stirring mixed liquid system is diluted, the mass percentage of the polyvinylidene fluoride porous microspheres is 5%-20%. For example, the mass percentage of the polyvinylidene fluoride porous microspheres is 5%, 8%, 10%, 12%, 15%, 16% or 20%.
[0072] In some embodiments, the stirring speed during sand milling is 500rpm-1500rpm, for example, the stirring speed during sand milling is 500rpm, 600rpm, 700rpm, 800rpm, 1000rpm, 1200rpm or 1500rpm. The stirring time is 5min-30min, for example, the stirring time is 5min, 10min, 15min, 20min, 25min or 30min. Controlling the sand milling time and the stirring speed of sand milling can further control the particle size of the porous microspheres after adsorption of the surfactant, so that when the slurry is prepared, the particle size will not be too small to affect the ion transport of the diaphragm, nor will it be too large to affect the thickness of the diaphragm, thereby affecting the energy density of the battery.
[0073] In some embodiments, the mass ratio of the polyvinylidene fluoride porous microspheres to the adhesive is 100:(5-15). That is, the mass percentage of the adhesive to the polyvinylidene fluoride porous microspheres is 5%-15%. For example, the mass percentage of the adhesive to the porous microspheres is 5%, 8%, 10%, 12% or 15%. Controlling the proportion of the adhesive can fully ensure the bonding force between the multiple porous microspheres, ensure the stability of the coating, and facilitate the realization of the coating function.
[0074] The technical solution of the present application is further described below through specific embodiments.
[0075] Embodiment 1
[0076] Preparation of porous polyvinylidene fluoride microspheres: The mass ratio of PVDF, PMMA, and PLLA is controlled to be 4.5:4.5:91, and the amount of compatibilizer P (MMA-co-GMA) added is 0.07% of the total mass of the mixture of PVDF, PMMA, and PLLA. First, PVDF, PMMA, PLLA, and the compatibilizer are dried in a vacuum drying oven at 80°C for 12 hours, and then PVDF, PMMA, PLLA, and the compatibilizer are added to an internal mixer by melt blending. The internal mixer temperature is 200°C, the rotor speed is 20rpm / min, and the premixing is 2min; then the rotor speed is increased to 50rpm / min, and the material is discharged after fine mixing for 10min, and cooled to room temperature. Then it is placed in an oven at a temperature of 200°C, melted for 10min, and then cooled to 145°C, and placed at this temperature for 24h to fully crystallize. The extraction was performed using the Soxhlet extraction method, the extracting solution was a good solvent (chloroform) for PLLA and PMMA, the heating temperature was controlled at 105°C, the extraction time was 10 hours, and the microspheres were taken out after the extraction, placed in ethanol for 2 hours, and then transferred to deionized water and placed for 2 hours to obtain wet PVDF porous microspheres. The wet PVDF porous microspheres were freeze-dried to obtain dry PVDF porous microspheres.
[0077] Preparation of the coating: 75% by mass of PVDF porous microspheres, 5% by mass of a surfactant and the remainder of deionized water were mixed, and the mixture was prepared by high-speed spiral stirring at a speed of 500 rpm for 3 hours. Then, water was added to dilute the mixed liquid system to a PVDF porous microsphere content of 10%, and then sand-milled at 800 rpm for 10 minutes. A polyacrylic acid (PAA) adhesive accounting for 10% by mass of the PVDF porous microspheres was added, stirred, and then sprayed on the polypropylene porous substrate layer.
[0078] Embodiment 2
[0079] The difference between this embodiment and the first embodiment is that the mass ratio of PVDF, PMMA and PLLA is 10:10:80.
[0080] Embodiment 3
[0081] The difference between this embodiment and the first embodiment is that the mass ratio of PVDF, PMMA and PLLA is 25:25:50.
[0082] Embodiment 4
[0083] The difference between this embodiment and the first embodiment is that no compatibilizer is added.
[0084] Embodiment 5
[0085] The difference between this embodiment and the first embodiment is that the amount of the compatibilizer added is 0.03%.
[0086] Embodiment 6
[0087] The difference between this embodiment and the first embodiment is that the amount of the compatibilizer added is 0.1%.
[0088] Embodiment 7
[0089] The difference between this embodiment and the first embodiment is that when the coating is prepared, in the mixed liquid system, the mass percentage of PVDF porous microspheres is the same as that of the first embodiment, the mass percentage of the surfactant is 1%, and the balance is deionized water.
[0090] Embodiment 8
[0091] The difference between this embodiment and the first embodiment is that when the coating is prepared, in the mixed liquid system, the mass percentage of PVDF porous microspheres is the same as that of the first embodiment, the mass percentage of the surfactant is 3%, and the balance is deionized water.
[0092] Embodiment 9
[0093] The difference between this embodiment and the first embodiment is that when the coating is prepared, in the mixed liquid system, the mass percentage of PVDF porous microspheres is the same as that in the first embodiment, the mass percentage of the surfactant is 7%, and the balance is deionized water.
[0094] Embodiment 10
[0095] The difference between this embodiment and the first embodiment is that when the coating is prepared, in the mixed liquid system, the mass percentage of PVDF porous microspheres is the same as that in the first embodiment, the mass percentage of the surfactant is 10%, and the balance is deionized water.
[0096] Embodiment 11
[0097] The difference between this embodiment and the first embodiment is that when the coating is prepared, in the mixed liquid system, the mass percentage of PVDF porous microspheres is the same as that in the first embodiment, the mass percentage of the surfactant is 15%, and the balance is deionized water.
[0098] Embodiment 12
[0099] The difference between this embodiment and the first embodiment is that when the coating is prepared, in the mixed liquid system, the mass percentage of PVDF porous microspheres is the same as that in the first embodiment, the mass percentage of the surfactant is 20%, and the balance is deionized water.
[0100] Embodiment 13
[0101] The difference between this embodiment and the first embodiment is that, when preparing the coating, the high-speed spiral rotation method is not used, and 10% polyvinylidene fluoride, 5% surfactant and 85% deionized water are directly added, sanded at 800 rpm for 10 minutes, and then 10% of the PAA adhesive accounting for the total amount of polyvinylidene fluoride is added, stirred and sprayed.
[0102] Embodiment 14
[0103] The difference between this embodiment and the first embodiment is that after the coating slurry is prepared, it is coated on the substrate layer by roller coating to form a coating layer.
[0104] Comparative Example 1
[0105] The difference between this comparative example and Example 1 is that commercially available polyvinylidene fluoride (average particle size 100 nm) is used to prepare the coating slurry, and the commercially available polyvinylidene fluoride is solid polyvinylidene fluoride microspheres without a porous structure on the surface.
[0106] Comparative Example 2
[0107] The raw materials of this comparative example are the same as those of comparative example 1, and commercially available polyvinylidene fluoride (average particle size 100 nm) is selected to prepare the coating slurry. The difference is that the high-speed spiral rotation method is not used in the specific preparation, and 10% polyvinylidene fluoride, 5% surfactant and 85% deionized water are directly added, sanded at 800rpm for 10min, and then 10% of the PAA adhesive accounting for the total amount of polyvinylidene fluoride is added, stirred and sprayed.
[0108] Comparative Example 3
[0109] The polypropylene porous substrate layer of Example 1 was directly used as a diaphragm for testing and comparison.
[0110] The battery separators of the above-mentioned embodiments and comparative examples were tested. The test method is as follows:
[0111] D50 particle size test of porous microspheres: BT-9300S laser particle size analyzer is used for determination. Deionized water is used as the dispersion medium. The sample is evenly dispersed through mechanical stirring. Ultrasonic high-frequency vibration is started to fully disperse the agglomerated particles. The test results are displayed in the form of particle size distribution data table, distribution curve, D10, D50, D90, etc.
[0112] Specific surface area test of porous microspheres: The specific surface area parameters of porous microspheres were analyzed using a fully automatic specific surface and void analyzer, and the specific surface area of the north side sample was calculated using the Brunauer-Emmett-Teller (BET) theoretical model.
[0113] Coating amount test: using MS105 electronic balance to measure, firstly cut the base film and coated diaphragm into 100mm×100mm samples, and then weigh them, the masses are M0 and M1 respectively, and the coating amount is calculated as: x=M1-M0.
[0114] Permeability test: measured using EG01-55-1MR permeability meter, expressed as the time taken for 100 mL of gas to pass through a fixed area diaphragm.
[0115] 80℃ Adhesion Test: Cut the diaphragm sample into 20mm×100mm strips, cut the positive electrode sheet into 20mm×100mm as the base plate, and the sample coating surface corresponds to the positive electrode surface. It should be flat and wrinkle-free when attached to the positive and negative electrode sheets. Then place it on a Teflon steel plate and heat press it for 60s at a pressure of 2MPa and 80℃ to make a test sample. Then use a tensile tester to test the bonding strength between the diaphragm and the electrode sheet.
[0116] 25℃ adhesion test: Cut the diaphragm sample into 20mm×100mm strips, cut the positive electrode sheet into 20mm×100mm as the base plate, and the coated side of the sample corresponds to the positive electrode side. It should be flat and wrinkle-free when attached to the positive and negative electrode sheets. Then place it on a Teflon steel plate and cold press it for 15s at a pressure of 3MPa and 25℃ to make a test sample. Then use a tensile tester to test the bonding strength between the diaphragm and the electrode sheet.
[0117] Wet adhesion test: Cut the diaphragm sample into 20mm×100mm strips, cut the positive electrode sheet into 20mm×100mm as the base plate, and the sample coating surface corresponds to the positive electrode surface. It should be flat and wrinkle-free when attached to the positive and negative electrode sheets, and then placed on a Teflon steel plate. Cold press for 15s at a pressure of 3MPa and 25℃ to make the test sample. After dripping 1mL of electrolyte on the sample, let it stand for 12h, and then use a tensile tester to test the bonding strength between the diaphragm and the electrode sheet.
[0118] The test data of the porous microspheres are shown in Table 1 below.
[0119] Table 1
[0120] Serial number D50(μm) <![CDATA[Specific surface area (m 2 / g)]]> Embodiment 1 1.22 35.79 Embodiment 2 4.53 24.46 Embodiment 3 9.03 19.04 Embodiment 4 2.54 28.04 Embodiment 5 1.67 31.50 Embodiment 6 1.08 37.11
[0121] The test data of the diaphragm is shown in Table 2 below
[0122] Table 2
[0123]
[0124] From the data comparison of Example 1 to Example 3 in Table 1, it can be seen that the increase in the amount of polyvinylidene fluoride and acrylic polymer added will increase the particle size of the porous microspheres and reduce the specific surface area.
[0125] From the comparison of the data of Examples 4 to 6 in Table 1 and Table 2, it can be seen that the addition of the compatibilizer further reduces the size of the microspheres, thereby preparing polyvinylidene fluoride (PVDF) porous microspheres with smaller size and better uniformity.
[0126] From the data comparison of Example 9 to Example 14 in Table 2, it can be seen that in the process of preparing the coating slurry, since polyvinylidene fluoride has super hydrophobic properties, as the amount of surfactant added increases, it helps to improve the adhesion of the coating and the substrate layer, thereby improving the stability of the diaphragm and solving the problem of coating shedding or powdering. However, with the further increase of surfactant, not only will polyvinylidene fluoride be too dispersed and single, which will reversely affect the bonding effect between the coating and the pole piece, but also because of its small molecular weight, the base film will be blocked, the permeability value of the coated diaphragm will increase, and the battery rate performance will be reduced.
[0127] It can also be seen from the data comparison in Table 2 that the spiral rotation method for preparing the coating slurry can improve the bonding effect between the diaphragm and the pole piece. At the same time, the use of polyvinylidene fluoride porous microspheres helps to achieve the bonding of the pole piece and the diaphragm at room temperature, thereby making it easier to control the production cost.
[0128] The above specific examples are used to illustrate the present application, which is only used to help understand the present application and is not intended to limit the present application. For technicians in the technical field to which the present application belongs, they can also make some simple deductions, deformations or substitutions based on the ideas of the present application.
Claims
1. A diaphragm coating slurry, characterized in that: The invention comprises polyvinylidene fluoride porous microspheres; the polyvinylidene fluoride porous microspheres have a narrow and long pore structure, and the average pore size of the polyvinylidene fluoride porous microspheres is less than 50nm.
2. The diaphragm coating slurry according to claim 1, characterized in that: The D50 particle size of the polyvinylidene fluoride porous microspheres is 1 μm-10 μm.
3. The diaphragm coating slurry according to claim 1, characterized in that: The melting point of the polyvinylidene fluoride porous microspheres is 80°C-130°C.
4. The diaphragm coating slurry according to any one of claims 1 to 3, characterized in that: The preparation method of the polyvinylidene fluoride porous microspheres comprises: Drying the polyvinylidene fluoride, the acrylic polymer and the lactic acid polymer; Melting and blending the dried polyvinylidene fluoride, the acrylic polymer and the lactic acid polymer according to a ratio, and then cooling the mixture to room temperature; The mixture cooled to room temperature is subjected to melting and cooling crystallization treatments in sequence to obtain a crystalline nanostructure; An extracting solution is added into the nanostructure to extract the acrylic polymer and the lactic acid polymer, so as to obtain the porous nanostructured polyvinylidene fluoride porous microspheres.
5. The diaphragm coating slurry according to claim 4, characterized in that: The preparation of the polyvinylidene fluoride porous microspheres further includes adding a compatibilizer to the polyvinylidene fluoride, the acrylic polymer and the lactic acid polymer according to a proportion, and then melt blending them.
6. The diaphragm coating slurry according to claim 5, characterized in that: When preparing the polyvinylidene fluoride porous microspheres, at least one of the conditions (1) to (5) is met: (1) The mass ratio of the polyvinylidene fluoride to the acrylic ester polymer is 1:0.3-1:3; (2) The mass ratio of the total mass of the polyvinylidene fluoride and the acrylic ester polymer to the mass ratio of the lactic acid polymer is 1:(1-11); (3) the mass percentage of the compatibilizer in the mixture of the polyvinylidene fluoride, the acrylic polymer and the lactic acid polymer is 0.01%-0.1%; (4) the acrylic ester polymer includes an acrylic ester copolymer including at least one of polymethyl methacrylate, polymethacrylate, polyethyl acrylate and polymethyl acrylate; (5) The lactic acid polymer includes at least one of dextrorotatory polylactic acid, levorotatory polylactic acid, racemic polylactic acid and optically inactive polylactic acid.
7. The method for preparing a diaphragm coating slurry according to any one of claims 1 to 6, characterized in that: The following steps are involved: The porous polyvinylidene fluoride microspheres, a surfactant and an adhesive are mixed and dispersed in a solvent to prepare the membrane coating slurry.
8. The method for preparing the diaphragm coating slurry according to claim 7, characterized in that: The method for preparing the diaphragm coating slurry comprises: The polyvinylidene fluoride porous microspheres, the surfactant and part of the solvent are mixed and stirred in a spiral rotating manner to prepare a mixed liquid system; The mixed liquid system is diluted with the remaining amount of the solvent and ground, and then the adhesive is added and stirred to form the membrane coating slurry.
9. The method for preparing the diaphragm coating slurry according to claim 8, characterized in that: The method for preparing the membrane coating slurry satisfies at least one of the conditions (1) to (4): (1) The solid content of the mixed liquid system is ≥56%; (2) In the mixed liquid system, the mass percentage of the surfactant is 1%-20%; (3) In the mixed liquid system, the mass percentage of the polyvinylidene fluoride porous microspheres is 55%-95%; (4) In the membrane coating slurry, the mass ratio of the polyvinylidene fluoride porous microspheres to the adhesive is 100:(5-15).
10. A battery separator, characterized in that: It comprises a porous substrate and a coating disposed on at least one surface of the porous substrate; the coating is prepared by using the diaphragm coating slurry as described in any one of claims 1 to 6 or the diaphragm coating slurry prepared by the preparation method as described in claims 7 to 9.
Citation Information
Patent Citations
Coating film composition for battery electrodes or separators, battery electrode or separator provided with coating film obtained by using same, and battery provided with battery electrode or separator
CN105027328A
Polyvinylidene fluoride hierarchical pore film with island structure and preparation method thereof
CN110615903A
Coated diaphragm and preparation method thereof
CN114361706A
Diaphragm and battery comprising same
CN116435713A
Diaphragm and secondary battery
CN116666905A